Specific and safe targeting of glioblastoma using switchable and logic-gated RevCAR T cells - Saleh, Haidy A.; Mitwasi, Nicola; Ullrich, Martin; Kubeil, Manja; Toussaint, Magali; Deuther-Conrad, Winnie; Neuber, Christin; Arndt, Claudia; R. Loureiro, Liliana; Kegler, Alexandra; González Soto, Karla Elizabeth; Belter, Birgit; et al. (Frontiers in Immunology, 2023)
Glioblastoma (GBM) is still an incurable tumor that is associated with high recurrence rate and poor survival despite the current treatment regimes. With the urgent need for novel therapeutic strategies, immunotherapies, especially chimeric antigen receptor (CAR)-expressing T cells, represent a promising approach for specific and effective targeting of GBM. However, CAR T cells can be associated with serious side effects. To overcome such limitation, we applied our switchable RevCAR system to target both the epidermal growth factor receptor (EGFR) and the disialoganglioside GD2, which are expressed in GBM. The RevCAR system is a modular platform that enables controllability, improves safety, specificity and flexibility. Briefly, it consists of RevCAR T cells having a peptide epitope as extracellular domain, and a bispecific target module (RevTM). The RevTM acts as a switch key that recognizes the RevCAR epitope and the tumor associated antigen, and thereby activating the RevCAR T cells to kill the tumor cells. However, in the absence of the RevTM, the RevCAR T cells are switched off. In this study, we show that the novel EGFR/GD2-specific RevTMs can selectively activate RevCAR T cells to kill GBM cells. Moreover, we show that gated targeting of GBM is possible with our Dual-RevCAR T cells, which have their internal activation and co-stimulatory domains separated into two receptors. Therefore, a full activation of Dual-RevCAR T cells can only be achieved when both receptors recognize EGFR and GD2 simultaneously via RevTMs, leading to a significant killing of GBM cells both in vitro and in vivo.